PEMBELAJARAN INOVATIF BERBASIS PJBL DENGAN MENGGUNAKAN PENDEKATAN TPACK PADA PEMBELAJARAN PAI - Febria Aswandi; Abdul Quddus (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Islamic Religious Education (PAI) faces complex challenges in integrating technology, pedagogy, and teaching material content. This research aims to explain the application of the Project-Based Learning (PjBL) model with the Technological Pedagogical and Content Knowledge (TPACK) approach to improve the quality of PAI learning. The study employs a qualitative research approach, with data collected through a literature review (Library Research) by analyzing various academic sources, including articles, scientific journals, and books. The findings suggest that teachers must be able to integrate PjBL with the TPACK framework effectively. To optimize PAI learning, educators need both theoretical knowledge and practical skills in utilizing PjBL and TPACK. This integration helps teachers understand how technology can be effectively used in the learning process—not only in terms of operating technological devices but also in comprehending how these tools enhance teaching and learning outcomes.